2020
DOI: 10.3390/molecules25184348
|View full text |Cite
|
Sign up to set email alerts
|

Thymol Encapsulated into HP-β-Cyclodextrin as an Alternative to Synthetic Fungicides to Induce Lemon Resistance against Sour Rot Decay

Abstract: Consumers demand the use of eco-friendly fungicides to treat fruit and vegetables and governmental authorities have unauthorized the application of chemical antifungals for the efficient control of sour rot. In the present research, the microwave irradiation (MW) method was used to encapsulate thymol into 2-hydroxylpropyl-beta-cyclodextrin (HP-β-CD) and the effect of these HP-β-CD on controlling sour rot in citrus fruit, caused by Geotrichum citri-aurantii, was evaluated. Amounts of 25 and 50 mM of HP-β-CD-thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
1
8
1
1
Order By: Relevance
“…Medina et al found that chitosan thymol nanoparticles in the edible film had a good inhibitory effect on Botrytis cinerea during the storage of blueberry fruits ( Medina et al, 2019 ). Thymol – HP-β-cyclodextrin microcapsules could control acid rot pathogen Geotrichum Citri-Aurantii in citrus fruits ( Serna-Escolano et al, 2020 ). The antifungal mechanism of thymol might be the inhibition of pathogen growth and spore germination, the direct effect on phospholipid and protein degradation ( Jung et al, 2021 ), and the inhibition of ergosterol biosynthesis to change the permeability of cell membrane and caused obvious damage to the cell wall and plasma membrane ( Galotto et al, 2016 ), cytoplasmic disintegration and organelle death ( Kowalczyk et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medina et al found that chitosan thymol nanoparticles in the edible film had a good inhibitory effect on Botrytis cinerea during the storage of blueberry fruits ( Medina et al, 2019 ). Thymol – HP-β-cyclodextrin microcapsules could control acid rot pathogen Geotrichum Citri-Aurantii in citrus fruits ( Serna-Escolano et al, 2020 ). The antifungal mechanism of thymol might be the inhibition of pathogen growth and spore germination, the direct effect on phospholipid and protein degradation ( Jung et al, 2021 ), and the inhibition of ergosterol biosynthesis to change the permeability of cell membrane and caused obvious damage to the cell wall and plasma membrane ( Galotto et al, 2016 ), cytoplasmic disintegration and organelle death ( Kowalczyk et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, thymol is unstable, water-insoluble and it has unsatisfactory properties. Encapsulation of thymol into microcapsules is one of the effective alternatives to overcome these shortcomings ( Serna-Escolano et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly used in the form of edible coating for fruit and vegetable preservation and disease prevention and control [34][35][36]. For example, Hp-β-cyclodextrin-encapsulated thymol microcapsules can be used as a substitute for synthetic fungicides to induce lemon resistance to sour rot decay; it has the effect of preventing and controlling fusculosis of citrus fruit [37]. The coating, which is composed of chitosan and thymol, can maintain the quality of fresh fig fruit, reduce the rate of fungal impregnation and decay, and extend the shelf life of fruit [38].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygenated aromatic compounds such as phenols (thymol, carvacrol, and eugenol), phenol ethers (trans-anethole and methyl chavicol), aldehydes (cinnamaldehyde, cuminaldehyde, and benzaldehyde), and aromatic acids (e.g., benzoic acid and cinnamic acid) exhibit both antibacterial and antifungal activities. ,, These compounds have been investigated for possible applications in food preservation as natural antifungal agents and in human and veterinary medicine as natural antimicrobial agents. , Recently, several reports have highlighted the feasibility of applying essential oils (EOs) for inhibiting spore germination and mycelial growth of G. citri-aurantii, including carvone, cinnamic acid, thymol, cinnamaldehyde, citral, and L-menthol . Simultaneously, EO treatment could increase the total phenol content and might lead to defense responses against G.…”
Section: Introductionmentioning
confidence: 99%
“…1,7,8 These compounds have been investigated for possible applications in food preservation as natural antifungal agents and in human and veterinary medicine as natural antimicrobial agents. 9,10 Recently, several reports have highlighted the feasibility of applying essential oils (EOs) for inhibiting spore germination and mycelial growth of G. citri-aurantii, including carvone, 11 cinnamic acid, 12 thymol, 13 cinnamaldehyde, 7 citral, 14 and L-menthol. 1 Simultaneously, EO treatment could increase the total phenol content and might lead to defense responses against G. citri-aurantii in citrus fruits.…”
Section: Introductionmentioning
confidence: 99%